Social Cognition in Schizophrenic Patients: The Effect of Semantic Content and Emotional Prosody in the Comprehension of Emotional Discourse - Brazo, Perrine; Beaucousin, Virginie; Lecardeur, Laurent; Razafimandimby, Annick; Dollfus, Sonia (Frontiers in Psychiatry, 2014)
Background : The recognition of the emotion expressed during conversation relies on the integration of both semantic processing and decoding of emotional prosody. The integration of both types of elements is necessary for social interaction. No study has investigated how these processes are impaired in patients with schizophrenia during the comprehension of an emotional speech. Since patients with schizophrenia have difficulty in daily interactions, it would be of great interest to investigate how these processes are impaired. We tested the hypothesis that patients present lesser performances regarding both semantic and emotional prosodic processes during emotional speech comprehension compared with healthy participants. Methods : The paradigm is based on sentences built with emotional (anger, happiness or sadness) semantic content uttered with or without congruent emotional prosody. The study participants had to decide with which of the emotional categories each sentence corresponded. Results : Patients performed significantly worse than their matched controls, even in the presence of emotional prosody, showing that their ability to understand emotional semantic content was impaired. Although prosody improved performances in both groups, it benefited the patients more than the controls. Conclusion : Patients exhibited both impaired semantic and emotional prosodic comprehensions. However, they took greater advantage of emotional prosody adjunction than healthy participants. Consequently, focusing on emotional prosody during carrying may improve social communication.